Social Group Dynamics as a Mechanism for Character Development Through Traditional Games: A Qualitative Study in Indonesian Elementary School - Yulianto, Irfan; Ningsih, Tutuk; Yahya, M Slamet (Papanda Publisher, 2025)
In the digital era, traditional games are increasingly marginalized despite containing essential social values for character formation. Limited empirical investigation exists regarding social group dynamics mechanisms through which character values are internalized. This research investigates social group dynamics in character development through traditional games, examining facilitation processes, group interaction patterns, and character value internalization mechanisms. This qualitative descriptive study was conducted at SD Negeri 5 Wangon, Indonesia, involving sixth-grade students and educational stakeholders. Data were collected through in-depth interviews, participant observation, and documentary analysis. Source triangulation and interactive analysis model ensured data trustworthiness. Four distinct facilitator functions emerged: communication, facilitation, motivation, and dynamization. Social group dynamics progressed through four phases—forming, storming, norming, and performing—each contributing uniquely to character internalization. Three traditional games (egrang, gobak sodor, engklek) developed specific character values: honesty, empathy, cooperation, sportsmanship, responsibility, and rule adherence. Sustained engagement catalyzed behavioral institutionalization, transforming discrete actions into habitual practices and ultimately stable character patterns. The Cheerful Traditional Games Movement exemplified successful institutionalization, demonstrating traditional games' viability as systematic character education interventions. Social group dynamics constitute powerful mechanisms for character development through traditional games. Strategic facilitation and sustained implementation enable authentic character formation transcending superficial behavioral compliance, offering culturally-grounded alternatives to conventional character education approaches.